Translocal Performance in Asian Theatre and Film - Tuan, Iris H. (Springer Singapore, 2018)
This pivot offers an innovative, trans-local perspective on performance studies in the era of digital technology, considering a range of content from theater to opera, film, dance, and musical theatre. It examines theatre performing arts and film in terms of aesthetics, gender studies, and identity politics, and showcases the value of human accomplishments in theatre and film and their representative artistic works. It also addresses key issues within performance studies, such as gender, class, race, ethnicity, identity, and how minorities portray their ethnicity stories. This book links the trans-national and the trans-local and considers how emerging mobile geographies and new methodologies of interpreting performance in theatre and film reflect the transformations of our understanding of geopolitical time and space.